A critical discussion of theoretical foundations and measurement methods of gender roles. (13th November 2019) - Jaehn, P; Cook, S; Holmberg, C
Abstract: Background: Public health researchers have frequently investigated associations of individual gender role norms or attitudes with a variety of health outcomes. It has been suggested that the construct of gender roles is multidimensional, including norms about gender inequality and gender-related division of labour. Implications of multidimensionality and limitations of applied measurement methods, however, have rarely been discussed critically in published studies. Methods: I will summarise theoretical considerations about the multidimensionality of the construct of gender roles. Examples of recently applied approaches to operationalise gender role attitudes in mental health research will be presented. The talk will conclude with a discussion of advantages and limitations of these approaches regarding consistency with theory, applicability, and reduction of measurement error. Results: Gender role norms include assumptions about inequality and division of labour in the public and private sphere. Items about gender role attitudes are regularly included in questionnaires of large social surveys and are suitable to explore associations with disease occurrence or quality of healthcare. Data reduction methods such as factor analysis might be applied to differentiate dimensions and to reduce measurement error. Conclusions: Shortcomings in considering theoretical foundations and inconsistencies in operationalisation might have contributed to the limited recognition of findings about possible impacts of gender roles on health. We need to advance measurement methods to increase the quality of public health research on gender. Finally, aspects of gender on the contextual level should complement investigations of individual gender roles.